Movement disorders, cerebral palsy and vaccination - Liba, Zuzana; Kraus, Josef; Necas, Tomas; Necas, Jiri; Klugar, Miloslav; Krsek, Pavel (European journal of paediatric neurology, 2022)
This review focused on vaccination in children with movement disorders, including cerebral palsy and the movement disorders triggered by vaccination in children with and without neurological disabilities. The following clinical questions were addressed: 1) Can children with movement disorders be vaccinated? 2) Can vaccination trigger movement disorders in children without neurological disabilities? 3) Can vaccination trigger movement disorders in children with neurological disabilities? and 4) Is there any consensus of care concerning vaccination in children with movement disorders? Following the PRISMA reporting guidelines, 1096 records were identified and 34 relevant papers were included. No evidence that vaccinations are contraindicated for children with movement disorders was noticed. Several reports of neurological adverse events, including movement disorders in children without neurological disabilities after various types of vaccination, were found. The reporting rates were low, the causality was controversial, and patient outcomes were mostly favourable. There was limited (if any) evidence in our search that any vaccination leads to any movement disorder exacerbation. Finally, no generally accepted consensus or standards of care concerning vaccination in patients with movement disorders were found. In summary, we found few precautions for vaccination in this group of patients and concluded that general best practice guidelines for immunization should be followed. In addition, influenza and pneumococcal vaccines are recommended because they can reduce morbidity and mortality in individuals severely affected by movement restrictions.
Keywords: chřipka lidská; vakcinace; Immunization; Influenza, Human; Child; lidé; vakcíny proti chřipce; pohybové poruchy; Influenza Vaccines; mozková obrna; Movement Disorders; Cerebral Palsy; dítě; Vaccination; Adverse events; Cerebral palsy; Movement disorders; Humans